“Danes Do It Melancholy”: Allusions to Shakespeare in Films and TV - Ranzato, Irene (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2017)
This contribution deals with source-text allusions to Shakespeare and to Shakespeare’s plays, which in either an overt or covert form are contained in dramatic dialogues and in visual elements in US-produced films and television shows. After a theoretical framing of the significance and import of allusions, the essay thus looks into the ways Shakespeare has been alluded to and explicitly quoted in a number of meaningful examples from American mainstream films and TV shows, with the purpose of evaluating the function of this type cultural references in the texts. When relevant, it also highlights if and how the creators of translations into Italian for the specific mode of dubbing have acknowledged this particular form of allusions and acted accordingly by keeping or omitting the intertextual references. Keywords: Shakespeare, allusion, translation, culture-specific references, dubbing, film and television studies